Magnetism and Optical Anisotropy in van der Waals Antiferromagnetic Insulator CrOCl - Zhang, Tianle; Wang, Yimeng; Li, Hexuan; Zhong, Fang; Shi, Jia; Wu, Minghui; Sun, Zhaoyang; Shen, Wanfu; Wei, Bin; Hu, Weida; Liu, Xinfeng; Huang, Li; et al. (ACS nano, 2019)
van der Waals (vdW) magnetic insulators are of significance in both fundamental research and technological application, but most two-dimensional (2D) vdW magnetic systems are unstable and of high lattice symmetry. Stable 2D vdW magnetic insulators with anisotropic structure are needed to modulate the properties and unlock potential applications. Here we present a stable vdW antiferromagnetic material, CrOCl, with low-symmetry orthorhombic structure, and investigate systematically its magnetism, phase transition behavior, and optical anisotropy. Spin–phonon coupling effects are uncovered by the abnormal frequency shifts of Raman-active modes, suggesting the formation of a magnetic superstructure. The sizable abnormal change of interplanar spacing indicates the presence of a structural transition at around 27 K. Further in-plane vibrational, reflectional, and absorptional anisotropic properties are explored both experimentally and theoretically, revealing a highly polarization sensitive characteristic and linear dichroism in 2D CrOCl. Meanwhile, the particularly high polarization dependency of the second-harmonic generation and the nonlinear susceptibility of ∼2.24 × 10–11 m/V make it suitable in the field of polarization-dependent nonlinear optics. The findings on the intricate properties of 2D CrOCl lay foundations for future applications of low-symmetry vdW magnets in spin-dependent electronic and optoelectronic devices.